Genome-wide identification of actin-depolymerizing factor gene family and their expression patterns under various abiotic stresses in soybean (Glycine max) - Sun, Yongwang; Wang, Deying; Shi, Mengmeng; Gong, Yujie; Yin, Shuwen; Jiao, Yexuan; Guo, Shangjing (Frontiers in Plant Science, 2023)
The actin-depolymerizing factor (ADF) encoded by a family of genes is highly conserved among eukaryotes and plays critical roles in the various processes of plant growth, development, and stress responses via the remodeling of the architecture of the actin cytoskeleton. However, the ADF family and the encoded proteins in soybean (Glycine max) have not yet been systematically investigated. In this study, 18 GmADF genes (GmADF1 – GmADF18) were identified in the soybean genome and were mapped to 14 different chromosomes. Phylogenetic analysis classified them into four groups, which was confirmed by their structure and the distribution of conserved motifs in the encoded proteins. Additionally, 29 paralogous gene pairs were identified in the GmADF family, and analysis of their Ka/Ks ratios indicated their purity-based selection during the evolutionary expansion of the soybean genome. The analysis of the expression profiles based on the RNA-seq and qRT-PCR data indicated that GmADFs were diversely expressed in different organs and tissues, with most of them responding actively to drought- and salt-induced stresses, suggesting the critical roles played by them in various biological processes. Overall, our study shows that GmADF genes may play a crucial role in response to various abiotic stresses in soybean, and the highly inducible candidate genes could be used for further functional studies and molecular breeding in soybean.